The psychological and aesthetic connotations of slow motion in the historical film (study in selected samples) (Journal of the College of Basic Education, 2023)
The slow motion in the film follows a series of natural shots and is unique in its psychological and aesthetic privacy to the spectator. Therefore, the research problem was an attempt to answer the following question:What are the psychological and aesthetic connotations of slow motion?The importance of research and the need for it:The importance of research and the need for it is evident in the fact that it deals with the subject of slow motion through its reliance on the most important ideas and theories stemming from the field of psychology and aesthetics.Search goal:The research aims to identify Mel Gibson's slow motion style, both psychologically and aesthetically.search limits :1. Temporal boundaries - the period from 1995-2004.2. Spatial borders - (United States of America).